Effect of Almond Skins on a Lung Injury Model Elicited by Multirug-Resistant Pseudomonas Aeruginosa. (May 2013) - Bisignano, C.; Esposito, E.; Filocamo, A.; Impellizeri, D.; Di Paola, R.; Mandalari, G.; Cuzzocrea, S.
A number of clinical trials have reported beneficial effects after nut consumption. The aim of the present work was to investigate the effect of natural almond skins (NS) on an animal model of acute pneumonia. Mice were inoculated with a multidrug-resistant strain of Pseudomonas aeruginosa (PA, 2 × 10 7 cfu's in 50 u.1 of lactated Ringer's solution) into their left lung. An oral administration of NS (30 mg kg 1 ) was given 1 h and 12 h after intra-tracheal PA inoculation. Mice were killed at 24 h for analyses of injury and inflammation. We investigated the effect of NS on the lung histology associated with PA, cytokine production, myeloperoxidase (MPO) activity and mortality caused by PA. Treatment with NS was effective in reducing the PA infection with a significant decrease in inflammation and lung injury. Significant inhibitions of the pro-inflammatory cytokines TNF-α and IL-12 and MPO activity were detected in mice which received NS compared with vehicle-treated animals. Treatment with NS reduced the overall mortality over the observation period (10 days). Almond skins were effective reducing the lung injury caused by PA inoculation in mice and may be useful in the treatment of antibiotic-resistant strains alone or in combination with existing antibiotics.